2008
DOI: 10.1016/j.vetpar.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoptic mange in red deer from Spain: Improved surveillance or disease emergence?

Abstract: Concern about emerging diseases has risen in recent years, and multihost situations have become increasingly relevant for wildlife management and conservation. We present data on Asturias, northern Spain, where 80 mangy red deer (Cervus elaphus) have been found since the beginning of the epizootic in chamois (Rupicapra pyrenaica parva) in 1993. We combine field and necropsy data with the results of a serosurvey using an in-house ELISA test to evaluate if deer mange due to Sarcoptes scabiei is an emerging disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 30 publications
(33 reference statements)
0
26
1
2
Order By: Relevance
“…This test detects the Ssλ20 antigen of the parasite, located in the mite's organs, the integument of the epidermis, and the spaces surrounding its vital organs (Casais et al 2007). This test was characterized by 100% sensitivity and 97% specificity in both red deer and southern chamois (Casais et al 2007), although field trials of the test in red deer revealed a slight decrease of specificity (97%) but a stronger decrease of sensitivity, which was 75% (Oleaga et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This test detects the Ssλ20 antigen of the parasite, located in the mite's organs, the integument of the epidermis, and the spaces surrounding its vital organs (Casais et al 2007). This test was characterized by 100% sensitivity and 97% specificity in both red deer and southern chamois (Casais et al 2007), although field trials of the test in red deer revealed a slight decrease of specificity (97%) but a stronger decrease of sensitivity, which was 75% (Oleaga et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that varieties of S. scabiei share common antigens which are recognized by antibodies of different species (Arlian et al, 1996). This ELISA has demonstrated specific antibodies to S. scabiei Ss20 B3 antigen in sera from mangy chamois, red deer, goats, pigs, and rabbits (Casais et al, 2007Oleaga et al, 2008;Falconi et al, 2010). The choice of assay format that we have selected responds to the small amount of antigen required (100 ng/well), its ease of production without using live animals and the good repeatability afforded by our recombinant antigen ELISA.…”
Section: Discussionmentioning
confidence: 73%
“…Sera were tested by an indirect ELISA (Casais et al, 2007), based on the S. scabiei recombinant antigen Ss20 B3 previously used for the immunodiagnosis of S. scabiei in different animal species (Casais et al, 2007Oleaga et al, 2008;Falconi et al, 2010). The ELISA was adapted for the diagnosis of the disease in rabbits by determining the optimal concentration of coating antigen, serum samples and conjugate (horseradish peroxidase-conjugated Protein A) performing a preliminary checkerboard titration using reference sera samples.…”
Section: Elisamentioning
confidence: 99%
“…In the UK, the surveillance of veterinary treatment residues in 643 sheep kidney fat samples in 1999 showed the presence of diazinon and propetamphos in 11 and 9 samples, respectively, with levels as high as 150 ng/g in the case of diazion (VMD, 2000). Such information highlights the need for further monitoring of antiparasitics in livestock carcasses left in the field for vultures or supplied at feeding stations; especially given that recent epizootics of mange in wild ungulates in Northern Spain (Oleaga et al, 2008) may result in higher use of antiparasitics in sheep and goat in future.…”
Section: Strategies For Risk Reductionmentioning
confidence: 99%